A Neat Way to Calculate the Gas Velocity from the Ergun Equation in a Packed Bed - Thomass Y. Choong; William R. Paterson; David M. Scott (ASEAN Journal of Chemical Engineering, 2004)
The Ergun equation is often used to describe the pressure drop in a packed bed. This paper presents a method to calculate neatly the gas velocity from the Ergun equation. This method is illustrated using rapid pressure swing adsorption, where flow resistance in the bed is crucial for the successful operation of the process.